ANALISIS PENGARUH RASIO SOLVABILITAS, STRUKTUR MODAL, DAN TANGGUNG JAWAB SOSIAL TERHADAP KINERJA KEUANGAN - Agus Munandar; Kesuma Dewi Safitri; Safira Putri Wulandari (Journal of Creative Student Research, 2023)
The purpose of this research is to determine the effect of solvency ratio, capital structure, and social responsibility on financial performance. This research uses 20 samples consisting of 5 companies in the cigarette industry subsector based on the time period 2018-2021. Data is collected from annual reports available on the Indonesia Stock Exchange (IDX). The analysis in this research uses 3 (three) approaches, including descriptive statistics, correlation, and regression. Based on the results of this research, it can be concluded that of the six elements, including ROA, ROE, DER, DAR, WC, and CSR, show good financial performance. In addition, DER and DAR measures negatively affect ROA and ROE. This is because the increase in solvency value causes the company's profit to decrease, it means that the company's high debt ownership makes the company pay higher interest so that the company's profit is small. WC and CSR have no impact on ROA and ROE. This is because the company's asset ownership can cover their current debt and CSR implementation can help convince interested parties to invest in the company. Based on the research conducted, the company should minimize the use of debt as funding in its operational activities, because it can affect the profitability of the company which causes a decrease in the value of ROA and ROE. In addition, the company should reconsider the implementation of CSR because it can help create a positive image of the company in the eyes of the public, even though the company's expenses will increase